Effect of packaging medium on survival of napier grass stem cutting - Jusoh, Shokri; Yaakub, H.; Hussein, N. H. (UB Press, 2016)
Napier grass (Pennisetum purpureum) is a species of perennial grass that has been used as ruminant feed because of high dry matter yield and most suitable for cut and carry to feed the animals. The napier stem also being traded among farmers and the planting materials has been sending via transportation and post. The problem begin when the purchased Napier grass stem cutting has to be hold for inspection and holding purpose. The plant can be wilt and half dead due to longer time before reach the customer‘s hand. The present study was conducted to generate new information regards on the best medium to be used for packaging plant stem cutting for postage and transportation purpose. The objective of the study is to identify the survival rate of Napier grass cutting after being pack in 5 different types of medium and keep for 1 month, where 100 mature Napier stem cutting, which consist of 50 samples of upper part and 50 samples of lower part in 5 different medium which are sawdust, paper wrapping, plastic wrapping, vacuum plastic and short immersion into fungicide. The entire packed Napier grass stem cuttings are then being postage and kept in the box for 1 month, and after 1 month of storage, the packed stem cutting was open and observed for the survival rate.